THE INFLUENCE OF FASHION TREND , PROMOTION AND LIFESTYLE ON DECISIONS TO PURCHASE OF TOKOPEDIA ONLINE PRODUCTS (Case Study on Generation Z in Rembang City) - Saesar Rio Daryanto; Ming Ming Lukiarti (SEAN Institute, 2023)
this study was to determine the effect of fashion trends , promotions and lifestyle on purchasing decisions for Tokopedia Online products (Case Study in Generation Z in Rembang District). Data collection techniques were carried out in this study through questionnaires. The data source used in the research conducted was primary data sources obtained from research instruments in the form of questionnaires filled out by respondents who distributed the questionnaires directly to consumers of Tokopedia's online products . The population of this study consisted of all consumers who had purchased and used Tokopedia online products in Rembang District. The sampling technique that is often used in research uses convenience random sampling , namely a sampling technique based on coincidence, that is, anyone who coincidentally or incidentally meets the researcher can be used as a sample . Based on the results of the study, it shows that promotion and lifestyle have a significant positive effect on purchasing decisions and fashion trends have a significant negative effect on purchasing decisions.